The application of E-commerce among small medium enterprises : a case study in Kelantan / Norudin Mansor, Che Ismail Long and Ahmad Ismail Mohd. Annuar - Mansor, Norudin; Long, Che Ismail; Mohd. Annuar, Ahmad Ismail (Institute of Research, Development and Commercialization (IRDC), 2007)
The research project was conducted to investigate the understanding of E-commerce Application among the SMEs in the state of Kelantan. Focusing on the population of registered members of Dewan Perniagaan Melayu Malaysia, Kelantan, a total of302 respondents were selected to participate in our study. Moving in line with the general assumption of world business community it is agreed that e-commerce application is highly relevant for the survival and meeting the challenges of borderless economy. At the same time, the process of acquiring knowledge and understanding the environment, coping with changes, and speeding up the business decision, able to further enhance the competitive advantage of the SMEs. Using the established model, our investigation focused on 5 identifiable variables to demonstrate its usefulness towards motivating SMEs to adopt e-commerce. Our analysis indicated that all the selected variables were significant towards enhancing the application of e-commerce and thus maintaining competitive advantage in the industry.